2005
DOI: 10.1590/s0102-79722005000100006
|View full text |Cite
|
Sign up to set email alerts
|

Obesidade e aspectos psicológicos: maturidade emocional, auto-conceito, locus de controle e ansiedade

Abstract: Resumo Investigou-se, neste trabalho, variáveis psicológicas como locus de controle, auto-conceito, ansiedade, maturação cognitiva e emocional e problemas comportamentais em crianças obesas e não obesas. Participaram do trabalho 54 crianças, com idades entre 10 e 12 anos, sendo 27 crianças obesas, 14 meninas e 13 meninos com índices de massa corporal situados acima do percentil 85, e 27 não obesas, 15 meninas e 12 meninos, com índices de massa corporal entre os percentis 5 e 85. Os grupos não se diferenciaram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
19

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 20 publications
0
11
0
19
Order By: Relevance
“…The authors found that the groups did not show any differences in terms of the variables studied, with evidence of psychological suffering in both groups, thus denying the association between obesity and psychological or behavioral problems. There are methodological differences between the present study and the study conducted by Cataneo, Carvalho and Galindo (26) , such as the study design and instrument used to assess the psychological factors, which makes it difficult to compare the findings. On the other hand, such differences suggest that further studies should be conducted with the purpose of identifying the actual interference of overweight/obesity in the psychological aspects of the QoL of adolescents.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The authors found that the groups did not show any differences in terms of the variables studied, with evidence of psychological suffering in both groups, thus denying the association between obesity and psychological or behavioral problems. There are methodological differences between the present study and the study conducted by Cataneo, Carvalho and Galindo (26) , such as the study design and instrument used to assess the psychological factors, which makes it difficult to compare the findings. On the other hand, such differences suggest that further studies should be conducted with the purpose of identifying the actual interference of overweight/obesity in the psychological aspects of the QoL of adolescents.…”
Section: Discussionmentioning
confidence: 80%
“…This context is even more disturbing when one takes into consideration that psychological problems, mainly depression, can increase the risk of developing and maintaining obesity during adolescence (25) . On the other hand, with the purpose of comparing psychological aspects in obese and eutrophic adolescents, Cataneo, Carvalho and Galindo (26) analyzed locus of control, self-concept, anxiety, cognitive and emotional maturation, and behavioral problems in 54 adolescents aged between ten and 12 years who lived in Ribeirão Preto, state of São Paulo, Brazil. The authors found that the groups did not show any differences in terms of the variables studied, with evidence of psychological suffering in both groups, thus denying the association between obesity and psychological or behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…Está ainda relacionada a diversos aspectos psicológicos, gerando sentimentos de insatisfação, ansiedade, não aceitação, inadequação e depressão, os quais podem constituir os maiores efeitos adversos da doença (8) . Este sentimento de inadequação e insatisfação, intimamente ligado aos transtornos de autoimagem e provocado pelo aumento de peso, pode provocar uma desvalorização do autoconceito no obeso, diminuindo a sua autoestima e dificultando sua relação com os outros e consigo mesmo (9) .…”
Section: Discussionunclassified
“…Studies has demonstrated the interaction of genetic and environmental factors, including socio-cultural factors, nutrition, smoking, alcohol consumption and physical activity [5].…”
Section: Discussionmentioning
confidence: 99%